Pusa caspica - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
16. Caspian Seal Pusa caspica French: Phoque de la Caspienne / German: Kaspi-Ringelrobbe / Spanish: Foca del Caspio Taxonomy. Phoca caspica Gmelin, 1788, “In mari, praesertim septentrionali, etiam Pacifico et Caspico [= Caspian Sea].” This species is monotypic. Distribution. Caspian Sea. Descriptive notes. Total length up to 150 cm (males) and 140 cm (females); weight 75-86 kg. Newborns are 65-80 cm in length and weigh c.5 kg. Male Caspian Seals are slightly larger than females when physically mature. Offspring are born with a long white lanugo (fine, soft hair) that they molt at ¢.3 weeks old;it is replaced by mostly uniformly gray hair. Adult Caspian Seals have dark spots on a lighter gray background dorsally and on a paler gray to white background ventrally, and adult males can also have scattered spotting ventrally compared with few ventral spots on adult females. Habitat. Restricted to the inland Caspian Sea in western Russia. Caspian Seals are often associated with ice that forms in the shallow northern part of the Caspian Sea in autumn and winter. Food and Feeding. The diet of the Caspian Seal is relatively diverse, depending on location. It includes some crustaceans in autumn and winter, and clupeid fish (Clupeonella spp.), sand smelts (Atherina boyeri caspica), carp, and Caspian roach (Rutilus rutilus caspicus) in spring and summer. Species of Clupeonella historically make up a major proportion of the total annual diet of the Caspian Seal. When Caspian Seals are in the Ural Estuary in autumn, they focus on carp, pike-perch (Sander lucioperca), and Caspian roach. Breeding. Caspian Seals are born on sea-ice from late January through early February and are weaned at 4-5 weeks old. Females bred shortly after their offspring are weaned in late February-March, or slightly earlier if they did not give birth that year. Females are sexually mature at aboutfive years old, but most females do not give birth for the first time until they are about seven years old. Males are sexually mature at ¢.6-7 years old. ...